Art and Geometry of Plants: Experience in Mathematical Modelling through Projects (2018)
ABSTARCT: This article presents some results of a qualitative-case study carried out with students in last year of secondary education (15 - 17 years) into an official educational institution. The research looked at learning outcomes through the development of mathematical modelling projects related to studying the distribution of the leaves and the growth of some plants. According to the results, when modelling projects grounded in studying the form and geometric magnitudes are carried out, students are able to find out the meaning of certain mathematical concepts and participate in activities to reach other processes such as exploration, representation, formal construction, and validation of mathematical results. Some implications for teaching and learning in classroom derive from this study, particularly, the need for students to face the project development articulating research and mathematical modelling.